Impact of water development on river flows and the catch of a commercial marine fishery. Issue 7 (24th July 2020) - Broadley, Andrew; Stewart‐Koster, Ben; Kenyon, Rob A.; Burford, Michele A.; Brown, Christopher J.
Abstract: The growing demand for freshwater resources has led to dam construction and water diversions in a majority of the world's large rivers. With an increasing demand for freshwater, trade‐offs between water allocations and the preservation of ecological connections between terrestrial and marine ecosystems are inevitable. The ecological links formed by rivers flowing into the ocean benefit many commercially fished species. The degree to which different species and the livelihoods of fishers are negatively impacted by changes in river flows due to water extraction or diversion is important for management across terrestrial and marine boundaries. Our objective was to predict how changes in freshwater flows from three wet–dry tropical rivers in northern Australia, that is, the Mitchell, Gilbert, and Flinders rivers, affect the commercial banana prawn ( Penaeus merguiensis ) catch. We used a novel spatiotemporal Bayesian approach to model the effects of river flows and key climate drivers on banana prawn catch. We then predicted how the loss of flow due to water extraction or diversion affected prawn catch. Our analyses of three water development scenarios found that catch was most impacted by water extraction during low flows. The impact of water extraction was greatest for a scenario with dams on the Mitchell River, where we predicted catch would decline by 53% during a year with low flow. Overall, our results imply that maintenance of low‐level flows is a crucial requirement for sustained fishery yields. We suggest that water managers must balance agricultural demand for water during drier years against the impact of water extraction on prawn fisheries during low‐flow years. Protecting low‐level flows during drier years is a priority for maintaining terrestrial–marine linkages for adjacent marine fisheries.